2019
DOI: 10.3390/foods8070244
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pulsed Electric Field on the Extraction of Bioactive Compounds from Beetroot

Abstract: Beetroot is a root vegetable rich in different bioactive components, such as vitamins, minerals, phenolics, carotenoids, nitrate, ascorbic acids, and betalains, that can have a positive effect on human health. The aim of this work was to study the influence of the pulsed electric field (PEF) at different electric field strengths (4.38 and 6.25 kV/cm), pulse number 10–30, and energy input 0–12.5 kJ/kg as a pretreatment method on the extraction of betalains from beetroot. The obtained results showed that the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 32 publications
1
48
0
3
Order By: Relevance
“…Therefore, this study confirms that, when used as a processing aid for potato, PEF does not result in detrimental effects on the properties of potato starch [6]. PEF has been shown to be effective in the extraction of bioactive compounds (mainly betalains) from beetroot, increasing the extraction yield [7]. The greatest increase in the content of betalain compounds in the red beet extract was noted when an electric field at 4.38 kV/cm was applied [7].…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Therefore, this study confirms that, when used as a processing aid for potato, PEF does not result in detrimental effects on the properties of potato starch [6]. PEF has been shown to be effective in the extraction of bioactive compounds (mainly betalains) from beetroot, increasing the extraction yield [7]. The greatest increase in the content of betalain compounds in the red beet extract was noted when an electric field at 4.38 kV/cm was applied [7].…”
supporting
confidence: 72%
“…PEF has been shown to be effective in the extraction of bioactive compounds (mainly betalains) from beetroot, increasing the extraction yield [7]. The greatest increase in the content of betalain compounds in the red beet extract was noted when an electric field at 4.38 kV/cm was applied [7]. The increase in the extraction rate of polyphenols from olive leaves was also observed by using high-voltage electrical discharges (HVED) as a green technology [8].…”
mentioning
confidence: 99%
“…Despite the large number of compounds referred to by the term betalains, the betacyanins that are found in the highest concentration in beetroot are, in decreasing order, betanin, isobetanin, neobetanin, and probetanin ( Figure 2). In the case of the betaxanthins present in beetroot, also in descending order, they are vulgaxanthin I, vulgaxanthin II, indicaxanthin, miraxanthin, and portulaxanthin ( Figure 3) [3,5,24,31]. Despite this, different studies have observed a large number of betalains in beetroot.…”
Section: Betalainsmentioning
confidence: 98%
“…Red beetroot ( Beta vulgaris L. species) is a source of bioactive compounds, including dietary NO 3 − , betanin, antioxidant substances, and phenolic compounds (PCs), as well as a source of dietary fiber, minerals (potassium, sodium, iron, copper, magnesium, calcium, phosphorus, and zinc) and vitamins (retinol, ascorbic acid, and B-complex) [ 3 , 10 ]. However, dietary NO 3 − supplementation from beetroot requires smart formulations, to provide convenient serving portions while also containing effective concentrations of NO 3 − and bioactive compounds as a feasible alternative to the consumption of whole in natura vegetables.…”
Section: Introductionmentioning
confidence: 99%